Regions supporting the spatial Development of Russia: budgetary Aspect - P. V. Stroev; M. V. Milchakov; O. V. Pivovarova (Финансы: теория и практика, 2021)
The authors investigate the prospects for the spatial development of modern Russia highlighting the supporting regions considered in the budgetary aspect. The relevance of the study is due to the insufficient evidence for the effectiveness of the current policy of “equalization”, as well as the need for breakthrough growth of the Russian economy within the framework of national development goals. The present paper aims to identify one of the key elements of the supporting framework of the spatial organization of Russia in terms of the level of fiscal capacity. The research methodology is based on the use of complex, statistical and comparative analyses. The authors used official data of Rosstat on the population, tax and non-tax revenues, gratuitous receipts in 2010 and 2019 by regions of Russia. The authors highlight the key aspects of the spatial development of the Russian economy in the regional context: human capital development, economic development, the functioning of spatial structures of various types, fiscal capacity, environmental component, location of information and communication infrastructure, and geopolitical position. The influence of the fiscal capacity parameter on the sustainable socio-economic development of the region is justified. The fiscal capacity index of the constituent entities of Russia is analyzed at the end of 2010 and 2019, the main trends are identified. The study presents a cartographic visualization of the Russian regions by per capita fiscal capacity for tax and non-tax revenues of the consolidated budgets in 2019. The authors carried out a comparative analysis of the revenues of consolidated regional budgets on the macro-regional level, as a result of which the leading regions were identified and their budget parameters described.The present paper outlines one of the key elements of the supporting framework of Russian spatial organization from the point of view of fiscal capacity and identifies potential regions supporting spatial development in the context of macro-regions. The authors conclude that the supporting framework of the spatial organization of Russia, formed by the level of fiscal capacity, characterizes the financial potential of the territories, which can contribute to the development of interregional cooperation, including through the use of mechanisms for ensuring “horizontal” inter-budgetary transfers and budget loans. The prospect for further research on this topic consists in assessing and shaping other elements of the spatial development of Russia and identifying, by uniting them, supporting regions that can stimulate the development of not only the semi-periphery and periphery of their macro-regions but also of the entire country.